Ứng dụng nanosilica biến tính phenyl trietoxysilan làm chất phụ gia cho lớp phủ bảo vệ chống ăn mòn - Dương, Nguyễn Thùy; Sơn, Nguyễn Anh; Trúc, Trịnh Anh; Xuân Hằng, Tô Thị (Vietnam Journal of Chemistry, 2015)
Nanosilica was prepared by hydrolysis of tetraethyl orthosilicate (TEOS) at low pH and then treated with phenyl triethoxysilane (PTES). Nanosilica and PTES treated nanosilica were characterized by Field Emission Scanning Electron Microscope (FESEM), infrared spectroscopy (IR) and thermal gravimetric analysis (TGA). The obtained results showed that the size of nanosilica and treated nanosilica is about 20 nm and PTES treated nanosilica more homogeneous and separated. The TGA analysis results showed that the organic matter on the  surface nanosilica is about 8 wt.%. Epoxy coatings and epoxy coatings containing 3 wt % of nanosilica and 3 wt % of PTES treated nanosilica were prepared and applied on carbon steel. Protective property of coatings was evaluated by electrochemical impedance spectroscopy (EIS). The results showed that the presence of PTES treated nanosilica significantly improved barrier property and corrosion protection of epoxy coating.